2019
DOI: 10.1159/000502765
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Combination of Vaccinium Macracarpon, Lycium barbarum L. and Probiotics (Bifiprost®) for the Prevention of Chronic Bacterial Prostatitis: A Double-Blind Randomized Study

Abstract: <b><i>Introduction:</i></b> To evaluate the efficacy of Bifiprost® + Serenoa Repens 320 mg versus Serenoa Repens 320 mg alone for the prevention of chronic bacterial prostatitis (CBP) due to enterobacteriaceae. <b><i>Methods:</i></b> Between September 2016 and September 2018, 120 patients with CBP at the National Institutes of Health (NIH type II) with recurrent infections due to enterobacteriaceae (<i>Escherichia Coli</i> and <i>Enterococcus fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…Unlike Vicari's study, in our study, we enrolled patients without any intestinal disease and we treated them with probiotics only. On the other hand, another Italian group, demonstrated that a 6 months treatment with probiotics plus Vaccinium Macracarpon and Lyciumbarbarum L., reduces the number of symptomatic episodes and improves the quality of life [21]. The efficacy of probiotics in the management of CBP could be related to the immune modulation of the bowel epithelium with the suppression of the low-grade inflammation [8,22] and with the decrease of uropathogens spreading through the bowel mucosa.…”
Section: Results In the Context Of Previous Studiesmentioning
confidence: 99%
“…Unlike Vicari's study, in our study, we enrolled patients without any intestinal disease and we treated them with probiotics only. On the other hand, another Italian group, demonstrated that a 6 months treatment with probiotics plus Vaccinium Macracarpon and Lyciumbarbarum L., reduces the number of symptomatic episodes and improves the quality of life [21]. The efficacy of probiotics in the management of CBP could be related to the immune modulation of the bowel epithelium with the suppression of the low-grade inflammation [8,22] and with the decrease of uropathogens spreading through the bowel mucosa.…”
Section: Results In the Context Of Previous Studiesmentioning
confidence: 99%
“…A double-blind randomized study by Chiancone et al , involving 120 patients with chronic bacterial prostatitis, found that the association of Bifiprost® and SPE 320 mg improved the prevention of the episodes of chronic bacterial prostatitis due to Enterobacteriaceae and ameliorated prostatitis-related symptoms after 6 months of therapy. 54 The long-term impact on the entero-urinary route was also seen 3 months after the end of the treatment.…”
Section: Clinical Application Of Spe In Urinary System Diseasesmentioning
confidence: 96%
“…Several in vitro experiments have shown that treatment of human prostate cancer cells with certain probiotic strains ( L. rhamnosus GG, L. acidophilus La-05, L. casei- 01, and Bifidobacterium animalis Bb-12) strongly induced apoptosis [42] , [43] , indicating the potential of probiotics to suppress prostate cancer. Furthermore, probiotics have been demonstrated to improve prevention of episodes and alleviate symptoms in chronic bacterial prostatitis caused by Enterobacteriaceae [44] . In addition, decreased bacterial load of E. coli and Enterococcus faecalis in urine cultures was observed after probiotic administration in prostatitis [45] .…”
Section: Male Reproductive Microbiomementioning
confidence: 99%